2018
DOI: 10.1080/21623945.2017.1394537
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue autophagy related gene expression is associated with glucometabolic status in human obesity

Abstract: Adipose tissue autophagy (AT) is associated with human obesity and increased metabolic risk. Recent findings establish a role for autophagy in lipid metabolism. Here, we compared the expression of autophagy-related and lipolysis genes in human abdominal subcutaneous AT (SCAT) in overweight/obese subjects (n = 17) with or without impaired glucose tolerance in comparison with lean normal glucose tolerant individuals (n = 9), and investigated the association between AT autophagy and lipolysis. Human multipotent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…Recently, we showed that increased expression of autophagic genes (i.e. ATG 5–12 and 7) in human subcutaneous AT, was associated with an impaired glucometabolic status [ 4 ]. Lysosomal degradation of the autophagic cargo is the final stage of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that increased expression of autophagic genes (i.e. ATG 5–12 and 7) in human subcutaneous AT, was associated with an impaired glucometabolic status [ 4 ]. Lysosomal degradation of the autophagic cargo is the final stage of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In adipose tissue, how autophagy is dys-regulated remains unsettled, with a general agreement that autophagy genes are overexpressed in adipose tissue, particularly in depots and in obesity sub-types that are more associated with metabolic dysfunction. [6][7][8] Yet, although autophagy, particularly in chronic diseases, may be regulated also at the gene expression level, 9,10 much more is known about its more rapid regulation by post-translational modifications and proteinprotein interactions. Indeed, while two independent groups suggested that autophagic activity (i.e., 'flux') is inhibited in adipose tissue, 11,12 at least four groups, including our own, provided evidence that the elevated gene expression of autophagy genes in adipose tissue manifests by increased autophagic flux.…”
Section: Introductionmentioning
confidence: 99%
“…The ATG12 mRNA has been positively correlated with raised BMI. More significant correlation has also been reported between ATG7 mRNA with waist/hip ratio (WHR) 57 . Further, altered endogenous glucocorticoid metabolism, including 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), which generates active cortisol from cortisone, and 5α-reductase (5αR), has also been reported in obesity.…”
Section: Fig 2: Autophagy Inducers In Health Carementioning
confidence: 88%
“…The lipophagy dys-regulation (inhibition of adipose tissue autophagy), is associated with human obesity 55 . High levels of glucagon, lesser insulin, lower amino acid availability are some of the factors to activate autophagy, through modulation of mTORor/and Akt-dependent pathways 56 .…”
Section: Fig 2: Autophagy Inducers In Health Carementioning
confidence: 99%